Learning from Home Activity Using Google Form Application toward Online Learning Assessment in Elementary School - Hadianti, Yeni; Musthafa, Bachrudin; Fuadah, Ulfah Samrotul (International Conference on Elementary Education, 2021)
The research is based on the urgency of Indonesian learning in the Covid-19 pandemic situation. In the covid-19 pandemic, some strenuous effort is needed to prevent or stop the virus spread. One action in dealing with the covid-19 pandemic situation is Learning from Home. One application that is used in Learning from Home is Google Form. This study aimed to determine the implementation of Learning from Home using Google Form application toward online learning assessment. The research used Pre- experimental design methods One Shoot Case Study type with grade 3 students of Cimahi City Elementary School as the research subject. The result showed that Learning from Home with google form application has the fluctuation in assessment result based on a theme with the same material delivery technic. This result means that variations of media are needed to increase learning online results.